Praktek Excessive Pricing Dalam Bisnis Maskapai Penerbangan Ditinjau Dari Hukum Persaingan Usaha - Utomo, Zanuba Rachmawati; Setyawati, Ria (Istinbath : Jurnal Hukum, 2023)
This study aims to analyze the practice of excessive pricing on airlines as a form of abuse of a dominant position from the perspective of business competition law. The practice of excessive pricing is a strategy of setting excessive and exploitative prices toward consumers. In this research, The researcher indicated unfair business competition associated with excessive pricing practices. In addition, the researcher also analyzed the impact of excessive pricing practices on consumers and business competition. The research method used is normative research with a doctrinal research approach. The study results show that many users of air transportation modes make airline business actors take advantage of these conditions to multiply company profits by selling tickets at very high prices exceeding the Excessive Pricing. However, in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, there is no explanation of whether excessive pricing practices abuse a dominant position or are just regular business activity. Therefore, this paper aims to analyze and simultaneously prove indications of unfair business competition by airline business actors through excessive pricing from the perspective of business competition law.